Implementation and Contribution of Sekolah Peternakan Rakyat (SPR) Towards the Success of Brahman Cross Cattle Maintenance in Bojonegoro Regency - Abriyanti, Wahyu Hari; Azizah, Siti; Kuswati, Kuswati (Journal of Agriprecision & Social Impact, 2026)
This study evaluates the implementation and contribution of the Sekolah Peternakan Rakyat (SPR) Program to Brahman Cross cattle farming in Bojonegoro Regency. A mixed-methods approach with a sequential explanatory design was applied, involving surveys, in-depth interviews, field observations, and document analysis of 20 SPR farmers. The results show that the program effectively improved farmers’ knowledge and technical competencies (knowledge scores ranging from 4.35–5.00). However, business expansion aspiration remained very low 1.15, indicating structural constraints beyond individual capacity enhancement. Technical performance of Brahman Cross cattle was fluctuating, particularly in reproductive indicators, and institutional capacity within the farmer group remained limited in managerial coordination and collective decision-making. These findings demonstrate that improvements in individual capacity do not automatically translate into sustainable business performance. Institutional strengthening and alignment between program design and smallholder conditions are essential to ensure long-term program effectiveness.